2017
DOI: 10.1016/j.ijscr.2017.04.011
|View full text |Cite
|
Sign up to set email alerts
|

A rare case report of vulvar necrotizing fasciitis in a healthy patient

Abstract: HighlightsNF should be considered regardless of atypical location and lack of associations.Clinical findings are important indicators when diagnosing NF.Immediate surgical intervention should be performed upon suspicion of NF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The key to successful management of patients with necrotizing soft tissue infections relies on early recognition, prompt and aggressive surgical debridement with targeted antibiotic therapy [ 3 , 10 , 14 ]. Early diagnosis of NF remains a challenge partly due to nonspecific skin findings causing it to be misdiagnosed as cellulitis [ 2 , 5 , 14 ]. This patient was initially managed as cellulitis prior to referral, and this delayed the diagnosis of NF.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The key to successful management of patients with necrotizing soft tissue infections relies on early recognition, prompt and aggressive surgical debridement with targeted antibiotic therapy [ 3 , 10 , 14 ]. Early diagnosis of NF remains a challenge partly due to nonspecific skin findings causing it to be misdiagnosed as cellulitis [ 2 , 5 , 14 ]. This patient was initially managed as cellulitis prior to referral, and this delayed the diagnosis of NF.…”
Section: Discussionmentioning
confidence: 99%
“…Kobayashi et al showed that delays in surgical treatment of > 12 h are associated with an increased number of surgical debridement, higher incidence of septic shock and acute kidney injuries in patients with necrotizing soft tissue infections [ 15 ]. Unusual location of soft tissue infections, lack of associated co-morbidities and/or risks factors, absence of any history of preceding trauma or an obvious breech in the continuity of skin or mucosa, or a low Laboratory Risk Indicator for Necrotizing Fasciitis (LRINEC) score thus excludes the diagnosis of NF [ 2 , 4 ]. Our patient presented no specific risk factors for NF and no history of initiating trauma or breech in skin continuity but however developed a life threating NF.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations